Alzheimer’s Facebook support groups: uses, gratifications and perceptions of information accuracy for caregivers - Mayes, Kathryn A. (Kansas State University, 2015)
This study was designed to explore how Alzheimer’s caregivers use Facebook support groups. Specifically it describes what kinds of activities caregivers engage in when in Facebook support groups, explores the motivation behind participation, and details perceived advantages and disadvantages of the groups. Whether Facebook support groups are considered a primary and accurate source of disease information was also explored. The study was qualitative in nature and consisted of 20 caregiver interviews, conducted via phone and Skype. Guided by uses and gratifications theory (Katz, Blumler & Gurevitch, 1974), the study employed six research questions to fully explore the experiences of caregivers in Facebook support groups. Generally speaking, the study identified the primary theme of community, and three subthemes including context, advice and emotional release/support. There were also significant findings on the primacy and accuracy of information. The ability to more fully understand these themes in the context of the caregiver experience will provide health care professionals with a foundation on which they can build effective ways to tap existing Facebook support groups and bolster support as the Alzheimer’s epidemic grows exponentially between now and 2050.
Keywords: Alzheimer's; Support groups; Facebook; Uses and gratifications; Social media; Health communication; Communication (0459)